Metal nanoparticle synthesis using supercritical alcohol - Kim, Jaehoon; Kim, Daewoo; Veriansyah, Bambang; Kang, Jeong Won; Kim, Jae-Duck (ELSEVIER SCIENCE BV, 2009)
Metal nanoparticles with uniform size distribution were synthesized in a low carbon number of supercritical alcohol without using reducing agents or surfactants. Nanoparticles of copper (Cu). nickel (Ni). and silver (Ag) were synthesized in supercritical methanol or supercritical ethanol at 300 bar, 400 degrees C and reaction time of 5 min. The supercritical alcohol acted both as reaction medium and as a reducing agent. The synthesized particles were spherical in shape. The average diameter of Cu, Ni, and Ag particles was 420 +/- 119 nm, 50 +/- 10 nm, and 390 +/- 114 nm, respectively. Crown Copyright (C) 2009 Published by Elsevier B.V. All rights reserved.
Keywords: COPPER NANOPARTICLES; REDUCTION; PARTICLES; WATER